2014
DOI: 10.1002/2014gl061429
|View full text |Cite
|
Sign up to set email alerts
|

Large conversion rates of NO2 to HNO2 observed in air masses from the South China Sea: Evidence of strong production at sea surface?

Abstract: Nitrous acid (HONO) plays important roles in tropospheric chemistry, but its source(s) are not completely understood. Here we analyze measurements of HONO, nitrogen dioxide (NO 2 ), and related parameters at a coastal site in Hong Kong during September-December 2012. The nocturnal NO 2 -to-HONO conversion rates were estimated in air masses passing over land and sea surfaces. The conversion rates in the "sea cases" (3.17-3.36 × 10 À2 h À1 ) were significantly higher than those in the "land cases" in our study(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
71
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 41 publications
(84 citation statements)
references
References 30 publications
10
71
3
Order By: Relevance
“…The black arrow represents a period in which the data were used to calculate the heterogeneous conversion rate of the NO 2 . obtained in a semi-rural area in Germany (Kleffmann et al (2003), but lower than the values at most other sites, including those in the PRD region: Xinken (Su et al, 2008a), Back Garden (Li et al, 2012), and Hok Tsui (a coastal background site in Hong Kong) (Zha et al, 2014). The low C HONO in TC might have been related to the large area of forest near the site.…”
Section: The Heterogeneous Conversion Of No 2 To Honomentioning
confidence: 69%
See 1 more Smart Citation
“…The black arrow represents a period in which the data were used to calculate the heterogeneous conversion rate of the NO 2 . obtained in a semi-rural area in Germany (Kleffmann et al (2003), but lower than the values at most other sites, including those in the PRD region: Xinken (Su et al, 2008a), Back Garden (Li et al, 2012), and Hok Tsui (a coastal background site in Hong Kong) (Zha et al, 2014). The low C HONO in TC might have been related to the large area of forest near the site.…”
Section: The Heterogeneous Conversion Of No 2 To Honomentioning
confidence: 69%
“…A recent study at a coastal site in Hong Kong reported a large rate of 3.3 Â 10 À2 h À1 in air traveling over the oceans (Zha et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Zha et al . [] recently reported a NO 2 ‐to‐HONO conversion rate of 3.17–3.36 × 10 −2 h −1 in air masses passing over sea surfaces, which is almost 3 times the rate over land surfaces (1.20–1.30 × 10 −2 h −1 ), at a clean coastal site in Hong Kong. Although the exact mechanism is not yet clear, formation of HONO on the ocean surface could be a nonnegligible contributor to atmospheric HONO in areas adjacent to the ocean such as Hong Kong.…”
Section: Methodsmentioning
confidence: 99%
“…The most commonly accepted new HONO source is the heterogeneous conversion from NO 2 to HONO on humid ground and particle surfaces, but whether the conversion mainly occurs on ground surfaces or on aerosol surfaces remains a subject of debate [ Kleffmann , ]. A recent study observed faster conversions of NO 2 in air passing over the sea surface, suggesting that oceans may contribute to the production of HONO [ Zha et al , ]. Direct emission from vehicles has also been identified as a source of HONO, with a molar emission ratio of HONO to nitrogen oxide (NO x ) ranging from 10 −4 to 10 −2 [ Kurtenbach et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…al., 2010). HONO can be heterogeneously formed via conversions of NO 2 (Reaction R1) on particle, land, and sea surfaces (Kleffmann, 2007;Zha et al, 2014), directly emitted by traffic and biological activities (Kurtenbach et al, 2001;Oswald et al, 2013), and formed via photolysis of nitric acid (Zhou et al, 2011). During the day, HONO is then photochemically converted into OH radicals and NO (Reaction R2), both of which have an impact on the oxidation capacity (Kleffmann, 2007).…”
mentioning
confidence: 99%